Synovial sarcoma - de Stefani, Eduardo (Cirugía del Uruguay, 1973)
Synovial sarcoma is a rare. tumor of periarticular soft parts of limbs. It is formed by synovial cells v1hich adopt two different types; a synovial element of epithelioid aspect covering inlets, forming pseudoacinus or simulating a membrane, in compact arrangement; and a fibromatous element with fusiform cells arranged in fascicles. Growth of tumor is relatively slow, metastasis is produced through the blood system, and very often infiltrating regional ganglia; this is a fact to be born in mind in surgery.